Antibiotic prescribing and antimicrobial resistance: An evaluation of clinical teachers’ knowledge, attitude and practices at a South African dental school - Suwayda Ahmed; Rukshana Ahmed; Razia Zulfikar Adam; Renier Coetzee (PLoS ONE, 2026)
Introduction Indiscriminate antibiotic prescribing in healthcare continues to make a significant contribution to increasing global antimicrobial resistance rates. This public health threat has the potential to cause 10 million deaths per year, if no action is taken to address this phenomenon. In light of escalating AMR rates, the World Health Organization recommended a Global Action Plan against AMR in 2015, which highlighted global attention to AMR. One of the objectives of the Global Action Plan is to improve knowledge of antimicrobial resistance through effective education and training. Studies have suggested gaps in the knowledge and practice of antibiotic prescribing among healthcare professionals and undergraduate students, including medicine, dentistry, nursing, pharmacology and veterinary science. The dental profession has been identified as being a major contributor of excessive antibiotic prescribing, accounting for approximately 10% of systemic antibiotic prescriptions globally. Clinical knowledge, skills and practice gained during undergraduate dental programs can influence the clinical practice and competency of future prescribers. Clinical teachers thus play a critical role in shaping undergraduate dental students’ prescribing behaviours. This translates to effective undergraduate healthcare programs which offer adequate education on antimicrobial resistance and rational antibiotic prescribing practices to ensure that students are well prepared prior to entering clinical practice. Aim To determine the knowledge, attitudes and practices related to antimicrobial prescribing and AMR awareness among clinical teachers at a dental faculty in South Africa. Methodology A quantitative, cross-sectional questionnaire-based study was conducted among clinical teachers at the Faculty of Dentistry, University of the Western Cape in South Africa during the period of 28 September 2024 till 24 March 2025. A non-probability convenience sampling method was used. Responses were captured on a Google spreadsheet and exported to IBM SPSS Version 30 for descriptive and chi-square analyses. Results Sixty-one clinical teachers participated in the study (75% female and 25% male), with an 87.1% response rate. Participants’ work experience ranged from less than 5 years (2%), 5–10 years (11%), 11–15 years (18%), to more than 15 years (69%). The most commonly prescribed antibiotic regimen was a combination of amoxicillin and metronidazole. Majority of respondents (90%) prescribed a 5-day course of antibiotics, suggesting consistency with recommended short-course therapy. In cases of penicillin allergy, clindamycin (62%) was the most favoured alternative, which is concerning, as clindamycin is associated with numerous adverse effects. The understanding of AMR among clinical teachers was positive, with 92% correctly identifying AMR as bacteria resisting the effects of antibiotic therapy. Ninety-five percent of respondents viewed antibiotic resistance as a growing concern. The results demonstrate strong awareness and adherence to antibiotic prophylaxis guidelines among respondents, with 100% reporting both awareness of and compliance with such guidelines. Conclusion The results reveal a range of knowledge, attitudes, and practices related to antibiotic prescribing and AMR awareness among clinical teachers, and indicate acceptable levels of knowledge and practice in various clinical scenarios, however certain identified prescribing practices may require targeted educational intervention. By strengthening antibiotic stewardship principles among clinical teachers, undergraduate prescribing practices can be further enhanced.